Rancang Bangun Sistem Informasi Website Menggunakan Metode Prototype pada UMKM Jasa Maklun Kaos Sablon dengan Infrastruktur Multi Platform Gratis - Irvan Suryaningrat Suryaningrat; Otong Rukmana (UNISBA Press, 2022)
Abstract. SMEs maklun screen printing t-shirt services are MSMEs that provide services for the production of screen printing t-shirts. The emergence of changes in current business conditions on the part of MSMEs and problems with the ordering information service system complicate the running of the business and can even make the business not get a good system value, of course there must be improvements to lead to an effective and efficient system. the problem is formulated